Renewables in GCC countries: the next frontier? - Haug, M (Oxford Institute for Energy Studies, 2014)
More than 20,000 people attended the 7th World Future Energy Summit in Abu Dhabi earlier this year. The buzz and excitement is understandable in view of the many initiatives announced. Are national and international investors, contractors, technology providers, and suppliers ready to scale up renewables in GCC countries? Are they ready to shoulder the learning and localization challenges? As most renewable technologies require subsidies for years to come, will the GCC policy makers deliver the expected markets AND incentives? The article briefly summarizes the GCC countries’ initiatives. It explores the challenge of sharing equitably the costs and risks of renewables technology development, market uptake, and local industrial development, with industry participants. The GCC countries may find that long-term commitment, flexibility, and localization of policies may offer cost effective or efficient solutions to this dilemma.